2013
DOI: 10.1111/jdi.12081
|View full text |Cite
|
Sign up to set email alerts
|

Serum arylhydrocarbon receptor transactivating activity is elevated in type 2 diabetic patients with diabetic nephropathy

Abstract: Aims/Introduction: Evidence is emerging that exposure to persistent organic pollutants (POPs) is a risk factor for obesity-related diseases and for diabetes mellitus (DM). We found that POPs could be measured by a cell-based arylhydrocarbon receptor (AhR)-dependent reporter assay. We tested if serum AhR transactivating (AHRT) activities are a risk factor for diabetic nephropathy in people with type 2 diabetes. Materials and Methods: We enrolled diabetic patients with normoalbuminuria (n = 36), microalbuminuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The liver UGT activity can be regulated by nuclear receptors. It has been reported that Ugt1a9 mRNA expression in the liver was markedly induced by activators of the aryl hydrocarbon receptor (AhR) , and the serum AhR ligand activities are higher in T2DM . Therefore, the significant increase in UGT1A9 activity observed in this study may be related to the activation of AhR in the diabetes mice model.…”
Section: Discussionsupporting
confidence: 49%
“…The liver UGT activity can be regulated by nuclear receptors. It has been reported that Ugt1a9 mRNA expression in the liver was markedly induced by activators of the aryl hydrocarbon receptor (AhR) , and the serum AhR ligand activities are higher in T2DM . Therefore, the significant increase in UGT1A9 activity observed in this study may be related to the activation of AhR in the diabetes mice model.…”
Section: Discussionsupporting
confidence: 49%
“…Higher levels of serum AHR agonists have previously been reported in smokers, 32 as well as in patients with diabetes, 33 especially with severe diabetic nephropathy. 34 The authors suggested increased level of serum AHR agonists as a risk factor for the progression of kidney disease. Indeed, the activation of AHR could lead to the impairment of renal function by podocyte aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggest they could be employed as a diagnostic marker of metabolic syndrome and T2DM. In fact, patients with complications from DM had higher serum AhR ligands levels, suggesting they might contribute to the development of diabetic complications as well [75].…”
Section: Summary and Clinical Considerations With Edcs-induced Mitochmentioning
confidence: 99%